1995
DOI: 10.1016/s0022-5223(95)70197-4
|View full text |Cite
|
Sign up to set email alerts
|

The influence of leukocyte filtration during cardiopulmonary bypass on postoperative lung function: A clinical study

Abstract: The accumulation of activated leukocytes in the pulmonary circulation plays an important role in the pathogenesis of lung dysfunction associated with cardiopulmonary bypass. Animal studies have demonstrated that the elimination of leukocytes from the circulation reduces postoperative lung injury and improves postoperative pulmonary function. We conducted a prospective randomized clinical study to evaluate whether postoperative lung function could be improved by use of a leukocyte filter during cardiopulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
1
6

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 23 publications
5
57
1
6
Order By: Relevance
“…This was supported by Johnson et al, who measured PaO 2 and intra-pulmonary shunt (Qs/Qt) and found both to be worse in controls, although only in the first 4 h post CPB [55]. Subsequent studies report no impact on pulmonary function post-operatively, using a variety of indices [9,26,43,44,46]. More recent studies, however, describe beneficial effects of leukofiltration.…”
Section: Pulmonary Function Palanzo Et Al Reported Bettermentioning
confidence: 83%
See 3 more Smart Citations
“…This was supported by Johnson et al, who measured PaO 2 and intra-pulmonary shunt (Qs/Qt) and found both to be worse in controls, although only in the first 4 h post CPB [55]. Subsequent studies report no impact on pulmonary function post-operatively, using a variety of indices [9,26,43,44,46]. More recent studies, however, describe beneficial effects of leukofiltration.…”
Section: Pulmonary Function Palanzo Et Al Reported Bettermentioning
confidence: 83%
“…Whereas some studies showed similar elastase levels in the filtered and control patients [9,10,46], others have unexpectedly showed higher elastase levels following leukocyte filtration [35,43,44] and suggested this reflects increased elastase release by neutrophils trapped within the filter, rather than a higher activation of neutrophils within the tissues. Chen et al demonstrated a reduction in MDA [52] following leukocyte filtration, as did Allen et al in cyanotic infants [59].…”
Section: Does Systemic Leukofiltration Reduce Markers Of Systemic Infmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors have been able to show, that reperfusion injury to cardiac and pulmonary tissue is diminished by leukocyte filtration in the arterial line [5,6] or the venous line [7], and that leukocyte filtration in the blood cardioplegia delivery system can improve myocardial protection [8]. Despite these promising results, postoperative complications including systemic immune response syndrome (SIRS), myocardial and pulmonary reperfusion injury, and cerebral damage remain critical issues [1,2,9].…”
Section: Introductionmentioning
confidence: 99%